Association of remnant cholesterol with sarcopenia in Korean adults: a nationwide population-based study using data from the KNHANES - Jang, Soo Yeon; Hwang, Soon-Young; Jang, Ahreum; Kim, Kyeong Jin; Yu, Ji Hee; Kim, Nam Hoon; Yoo, Hye Jin; Kim, Nan Hee; Baik, Sei Hyun; Choi, Kyung Mook (Frontiers in Endocrinology, 2024)
Background: Mounting evidence indicates the importance of the interplay between skeletal muscles and lipid metabolism. Remnant cholesterol (remnant-C) is considered one of the principal residual risk factors for cardiovascular disease and metabolic disorders; however, there are limited studies on the impact of remnant-C on sarcopenia.Methods: Data from the Korea National Health and Nutrition Examination Surveys (KNHANES) between 2008 and 2011 were used in this nationwide population-based study. In total, 17,408 participants were enrolled in this study. The subjects were categorized into four groups according to the quartile of remnant-C values. We conducted multivariable logistic regression analysis to evaluate the association between remnant-C and muscle mass measured using dual-energy X-ray absorptiometry.Results: A total of 1,791 participants (10.3%) presented low muscle mass, and there was a sequential increase in the percentage of low muscle mass across remnant-C quartiles (Q1, 5.2%; Q2, 8.7%; Q3, 11.5%; Q4, 15.7%). In the full adjusted model, those in the highest remnant-C quartile group showed significantly increased odds ratio (OR) for low muscle mass compared with those in the lowest remnant-C group after adjusting for various confounding factors (OR = 1.33, 95% confidence interval (CI) = 1.06-1.68, P <0.05). A wide range of subgroups and sensitivity analyses showed consistent results, supporting the robustness of our findings.Conclusions: Increased remnant-C value was associated with a high risk of low muscle mass in the Korean population. Remnant-C may be a novel marker for the prediction and management of sarcopenia in aging societies.